Prognozowanie upadłości firm modelami analizy dyskryminacyjnej na przykładzie wybranych spółek giełdowych sektora przemysłu - Żurakowska-Sawa, Joanna; Hodun, Magdalena (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2012)
The bankruptcy of companies is a natural event of any economic activity. The main goal of this paper was to research insolvency risk chosen enterprises using discriminant analysis models. In this article characteristic and results of seven chosen discriminant models were presented.